PENGARUH UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA) - Chaerunnisa Rumianti (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
This study aims to test and analyse the Company Size and Liquidity Influence the Capital Structure (Studies in Manufacturing Companies in the Food and Beverage Sector in the Indonesia Stock Exchange). Data collection uses secondary data. The population in this study is the financial statements of all companies included in the food and beverage manufacturing sector listed on the Indonesia Stock Exchange from 2014-2016 taken by purposive sampling method, there are 42 samples from the financial statements of the Manufacturing Company in the Food and Beverage Sector in the Indonesia Stock Exchange. The financial statements have been tested for classic assumptions in the form of assumptions of normality, heteroscedasticity and multicolonality. Data analysis method uses multiple regression techniques. The results showed that based on the t-test, the variable of firm size has no effect and insignificant effect on the capital structure and the variable liquidity had a positive and significant effect on the capital structure. In the F test (simultaneous) the size of the company and liquidity have a positive and significant effect on the capital structure (Study in Manufacturing Companies in the Food and Beverage Sector in the Indonesia Stock Exchange).